Revisão das seções Acarporophytum, Aristata e Macrospora do gênero Batrachospermum (Rhodophyta, Batrachospermales) - Garcia Filho, Auro Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
he three sections of the genus Batrachospermum - Acarposporophytum (with the single species B. brasiliense Necchi), Aristata (B. beraense Kumano, B. cayennense Montagne, B. longiarticulatum Necchi and B. turgidum Kumano) and Macrospora (B. equisetifolium Montagne, B. hypogynum Kumano & Ratnasabapathy and B. macrosporum Montagne) – have been shown to be monophyletic in phylogenetic studies involving at least one member of each section. The following hypotheses were tested: 1) the sections Acarposporophytum, Aristata and Macrospora represent monophyletic groups within the genus Batrachospermum; the sections have been shown to be monophyletic and closely related in previous studies and with the addition of more species and populations this trend will be confirmed; 2) most species currently recognized in each section on the basis of morphological characters will be corroborated by molecular data. This revision of the three sections has the following aims: 1) to infere phylogenetic relationships and the intra-specific limits of variation of the species within and between sections, as well as with the other sections of the genus; the investigation used the morphological diagnostic characters currently applied and three molecular markers - rbcL, the plastidial gene encoding the large sub-unit of RUBISCO; the barcode region of the mithocondrial gene cox1, encoding sub-unit 1 of cythochorme c oxidase; and UPA, plastidial universal plastid amplicon; 2) to carry out a revisional study of the three sections by means of the reevaluation of taxonomic diagnostic characters for species within these groups, in the light of new molecular data. Nineteen new samples were analysed from the southeast, mid-west, north and northeast regions of Brazil, as well as the type specimens of each species and the sequences available in GenBank for each molecular marker. The diagnostic characters for section circumscription and species identification within the sections...

As três seções do gênero Batrachospermum - Acarposporophytum (com uma única espécie, B. brasiliense Necchi), Aristata (B. beraense Kumano, B. cayennense Montagne, B. longiarticulatum Necchi e B. turgidum Kumano) e Macrospora (B. equisetifolium Montagne, B. hypogynum Kumano & Ratnasabapathy e B. macrosporum Montagne) têm sido demonstradas como monofiléticas em estudos filogenéticos envolvendo pelo menos um representante de cada seção. As seguintes hipóteses foram testadas: 1) as seções Acarposporophytum, Aristata e Macrospora constituem grupos monofiléticos dentro do gênero Batrachospermum; as seções têm sido demonstradas como monofiléticas em estudos filogenéticos e com a adição de maior número de espécies e populações essa tendência deverá ser confirmada; 2) A maioria das espécies atualmente reconhecidas em cada seção com base em caracteres morfológicos será corroborada pelos dados moleculares. A presente revisão das três seções teve como objetivos: 1) inferir as relações filogenéticas, bem como os limites de variação intraespecíficas, das espécies dentro e entre as seções, bem como com outras seções do gênero, foram utilizados os caracteres morfológicos diagnósticos atualmente aceitos e três marcadores moleculares - rbcL, gene plastidial que codifica a subunidade grande da RUBISCO; região de “barcode” do gene mitocondrial cox1, que codifica a subunidade 1 da enzima citocromo c oxidase; e UPA - gene plastidial “universal plastid amplicon”; 2) elaborar estudo de revisão para as três seções por meio da realização dos caracteres taxonômicos diagnósticos para espécies desses grupos, à luz dos novos dados moleculares. Foram analisadas 19 amostras provenientes das regiões sudeste, centro-oeste, norte e nordeste do Brasil, além dos espécimes-tipo de cada seção e sequências disponíveis no “GenBank” para cada um dos marcadores utilizados. Os caracteres diagnósticos para o...
Keywords: Algae; Alga; Alga vermelha; Filogenia; Taxonomia vegetal; Biologia molecular